Revolutionizing Shopping Experience: The Impact of Mobile Apps on Customer Loyalty in Indonesian E-Commerce Market - Mohamad Trio Febriyantoro; Anton Kurniawan (International Journal of Economics, Business and Innovation Research, 2023)
The aim of this research is to assess the impact of perceived ease of use and perceived usefulness on customer satisfaction to build on the continuance intention of mobile shopping in Indonesia. The sample used in this study was 255 respondents from people living in Jakarta City who used a mobile shopping application. The approach used for data analysis in this research is based on Structural Equation Modeling (SEM) with version 3.0 of the SmartPLS. The results showed that perceived ease of use and perceived usefulness had a major impact on customer satisfaction, and that customer satisfaction had a positive impact on continuance intention. Based on the empirical results, it can be concluded that the perceived ease of use and perceived usefulness of the application platform is an influence on customer satisfaction to construct on sustainable consumption.